Species Distribution Model for the Asian Tapir and Vegetation Characteristics of Batang Gadis National Park, North Sumatra, Indonesia - Wanda Kuswanda; Freddy Jontara Hutapea; Muhammad Hadi Saputra; Bobby Nopandry (Tropical Life Sciences Research, 2022)
The Asian tapir is a primitive mammal whose habitat is heavily fragmented due to human activities. Studies on the Asian tapirs in Sumatra are very few, thereby basic information for developing tapir conservation programmes is limited. This study aimed to develop the species distribution model to map the potential distribution of tapirs in Batang Gadis National Park (BGNP), investigate the characteristic of tapir habitat, and identify tapir feed plants around BGNP. The model was developed using the Maximum Entropy (Maxent) approach, based on the existing information on tapir occurrence in BGNP and environmental variables. Vegetation characteristics in different land cover (primary forests, secondary forests, and open fields) were investigated using the strip transect method. This study found that zonal classification, temperature and precipitation have the greatest percentage contribution to the model. The model estimated that around 24.45% of BGNP areas are suitable for tapir habitat, and tapirs distribute near community gardens. Our results also showed that plant diversity at study sites was categorised as moderate-high. About 23 plant species dominated by the Moraceae family were identified as feed plants for tapirs. In developing tapir conservation programmes, BGNP management needs to consider tapir distribution that is closed to community gardens. We propose BGNP to enrich feed plants in open fields of the wilderness and traditional zones; reduce the canopy cover in the wilderness and utilisation zones to stimulate the growth of feed plants; facilitate local people to live harmoniously with tapirs; involve local communities in tapir conservation programmes; encourage local communities to plant non-palatable crops for tapirs; and provide a compensation scheme.